[18]Annulene put into a new perspective. - Lungerich, Dominik; Nizovtsev, Alexey; Heinemann, Frank Wilhelm; Hampel, Frank; Meyer, Karsten; Majetich, George; Schleyer, Paul V. R.; Jux, Norbert (Chemical Communications, 2016)
New insights into [18]annulene were gained by looking more closely at its X-ray structure, revealing a close face-to-face stacking of 3.16 Å in a herringbone-like crystal packing. Hexadehydro[18]annulene was co-crystalized in a benzene matrix, demonstrating the stabilizing role of intercalated solvent molecules in solid annulenes.